The two negetive points of the block add thise to you answer
-6 - 3 = -9
12 - (-6) = 18
4 - 12 = -8
20 - 4 = 16
The first difference is -9. The third difference is -8.
Maybe the fifth difference is -7.
That makes the next term 13.
<span>3, -6, 12, 4, 20, 13</span>
Answer:
Step-by-step explanation:
-y = -2x + 3
y = 2x - 3
y - 1 = 2(x - 1)
y - 1 = 2x - 2
y = 2x - 1
answer is B
Step-by-step explanation:
Here we are given that , the Value of
And we need to find the prove that ,
We know a identity as ,
On cubing both sides of the given equation,
Simplify and then substitute ,
Hence Proved !